Effect of systemic insulin treatment on diabetic wound healing. Issue 2 (20th February 2017) - Vatankhah, Nasibeh; Jahangiri, Younes; Landry, Gregory J.; Moneta, Gregory L.; Azarbal, Amir F.
Abstract: This study investigates if different diabetic treatment regimens affect diabetic foot ulcer healing. From January 2013 to December 2014, 107 diabetic foot ulcers in 85 patients were followed until wound healing, amputation or development of a nonhealing ulcer at the last follow‐up visit. Demographic data, diabetic treatment regimens, presence of peripheral vascular disease, wound characteristics, and outcome were collected. Nonhealing wound was defined as major or minor amputation or those who did not have complete healing until the last observation. Median age was 60.0 years (range: 31.1–90.1 years) and 58 cases (68.2%) were males. Twenty‐four cases reached a complete healing (healing rate: 22.4%). The median follow‐up period in subjects with classified as having chronic wounds was 6.0 months (range: 0.7–21.8 months). Insulin treatment was a part of diabetes management in 52 (61.2%) cases. Insulin therapy significantly increased the wound healing rate (30.3% [20/66 ulcers] vs. 9.8% [4/41 ulcers]) ( p  = 0.013). In multivariate random‐effect logistic regression model, adjusting for age, gender, smoking status, type of diabetes, hypertension, chronic kidney disease, peripheral arterial disease, oral hypoglycemic use, wound infection, involved side, presence of Charcot's deformity, gangrene, osteomyelitis on x‐ray, and serum hemoglobin A1C levels, insulin treatment was associated with a higher chance of complete healing (beta ± SE: 15.2 ± 6.1, p  = 0.013). Systemic insulin treatment can improve wound healing in diabetic ulcers after adjusting for multiple confounding covariates.